The Vertical Sense of Place in the Fiction of Barry Hannah and Flannery O’Connor - Kleppe, Sandra Lee (Nordlit, 1998)
In Barry Hannah’s novel Ray, the protagonist by the same name is simultaneously a Vietnam and a Civil War veteran and his memory is cluttered with events from both wars.